Pulmonary vein narrowing after visually guided laser balloon ablation: Occurrence and clinical correlates - Yamamoto, Tasuku; Takahashi, Yoshihide; Yamaguchi, Junji; Sekigawa, Masahiro; Shirai, Yasuhiro; Tao, Susumu; Hayashi, Tatsuya; Takigawa, Masateru; Goya, Masahiko; Sasano, Tetsuo (Journal of cardiovascular electrophysiology, 2020)
Introduction There are limited data focusing on pulmonary vein (PV) narrowing following ablation using a visually guided laser balloon (VGLB). We sought to assess the frequency and predictors of PV narrowing after VGLB ablation. Methods and Results Patients with paroxysmal atrial fibrillation treated with VGLB were screened. Study participants underwent contrast‐enhanced computed tomography (CT) scanning before and 6 months after the procedure. We defined 25% to 49%, 50% to 74%, and 75% to 100% reduction in PV cross‐sectional area as mild, moderate, and severe narrowing, respectively. Of 146 PVs in 38 patients analyzed, severe narrowing developed in two right superior and one right inferior PV. Moderate or severe narrowing occurred in 40 veins (27% of all PVs, 50% of the right superior, 22% of the right inferior, 21% of the left superior, and 14% of the left inferior PV). In PVs with moderate‐severe narrowing, the baseline orifice area was significantly larger (4.1 [interquartile range, 3.2‐4.8] vs 2.5 [1.9‐3.3] cm2, P < .0001), the narrowest region of stenosis was significantly more distal into the vessel (1.9 [0.7‐2.9] vs 0 [0‐1.7] mm from the orifice, P = .0006) and the total amount of energy delivered per vein was significantly greater (5190 ± 970 vs 4626 ± 1573 J, P = .018) than in PVs with mild or no significant narrowing. The baseline orifice area independently predicted moderate‐severe narrowing in multivariate analysis (odds ratio, 1.8 [1.3‐2.5] per 1 cm2 increase, P = .0003). No patient exhibited any signs or symptoms of PV stenosis. Conclusions Baseline PV orifice area, ablating distally inside the veins, and total amount of laser energy are associated with PV narrowing after VGLB ablation.